Prospective Study Comparing Clinicians' and Cancer Patients' Estimates of Risk of Relapse and Toxicity with Adjuvant Chemotherapy. (14th September 2021) - Calderon, Caterina; Jiménez-Fonseca, Paula; Hernández, Raquel; Muñoz, María del Mar; Martínez de Castro, Eva; Higuera, Oliver; Ghanem, Ismael; Castelo, Beatriz; Rogado, Jacobo; Carmona-Bayonas, Alberto
Abstract: The aim of this study was to compare physicians' and patients' estimates of risk of relapse and toxicity. A prospective, cross-sectional, multicenter study including 735 patients with cancer and 29 oncologists. Physicians' appraisals of risk of relapse with and without chemotherapy (27.5% and 43.1%) and risk of severe toxicity (12.2%) were more realistic than those of patients (34.6%, 78.5%, and 57.4%, respectively). The greater the risk of recurrence and risk of toxicity estimated, the less physicians expressed satisfaction with SDM. Estimations of risk of relapse and toxicity are important in diagnostic and therapeutic decision-making and can help patients face their situation.